Розширення діапазону регулювання вхідної реактивної потужності матричних перетворювачів засобами керування - Михальський, В.М.; Соболєв, В.М.; Шаповал, І.А.; Чопик, В.В. (Технічна електродинаміка, 2012)
The features of the matrix converter control to achieve the maximum expansion of the input reactive power control range have been considered. It is shown that the identity of the mathematical interpretation of additional degrees of freedom in the solution of transfer equations, despite their different implementation.